A foundational ontology for the modelling of manufacturing systems. (October 2018) - Zaletelj, Viktor; Vrabič, Rok; Hozdić, Elvis; Butala, Peter
Abstract: Models of distributed manufacturing systems cannot be consistent without a formal ontology. In this paper, the ontology formulation and maintenance are addressed in the scope of a collaborative modelling environment – in which concurrency, consistency, and model life cycle management should be supported. Thus, an extensible foundational ontology for manufacturing – system modelling is proposed in which the formal definitions of the modelling environment itself enable the definition of the manufacturing system's elements. The presented approach ensures the consistency of ever-changing models. The ontology is integrated into a modelling framework through the concept of description layers that assist in the management of the model description's complexity. The feasibility of the approaches is illustrated in an industrial case study that models of a manufacturing system for material processing.